2018
DOI: 10.1002/jbm.b.34283
|View full text |Cite
|
Sign up to set email alerts
|

An antibiofilm coating of 5‐aryl‐2‐aminoimidazole covalently attached to a titanium surface

Abstract: Biofilms, especially those formed by Staphylococcus aureus, play a key role in the development of orthopedic implant infections. Eradication of these infections is challenging due to the elevated tolerance of biofilm cells against antimicrobial agents. In this study, we developed an antibiofilm coating consisting of 5-(4-bromophenyl)-N-cyclopentyl-1-octyl-1H-imidazol-2-amine, designated as LC0024, covalently bound to a titanium implant surface (LC0024-Ti). We showed in vitro that the LC0024-Ti surface reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 69 publications
(88 reference statements)
2
19
0
Order By: Relevance
“…For example, an inhibitor might be given prophylactically to inhibit Salmonella colonization in the gut when the risk of exposure to Salmonella is high, as is currently done with probiotics 72 and vaccines 73 . The potential for clinical application is further supported by our recent reports showing that 2-aminoimidazoles can inhibit biofilm formation in vivo in a subcutaneous model in rats 14 , have low cytotoxicity against different mammalian cell types (tumor cell lines and bone cells 35,74 ) and do not affect the survival of Caenorhabditis elegans, a small nematode that is widely used for toxicity testing and is considered to have high predictive value for toxicity in mammals 75 . However, while clinical potential clearly exists, the assays we report here are most reflective of industrial treatments.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…For example, an inhibitor might be given prophylactically to inhibit Salmonella colonization in the gut when the risk of exposure to Salmonella is high, as is currently done with probiotics 72 and vaccines 73 . The potential for clinical application is further supported by our recent reports showing that 2-aminoimidazoles can inhibit biofilm formation in vivo in a subcutaneous model in rats 14 , have low cytotoxicity against different mammalian cell types (tumor cell lines and bone cells 35,74 ) and do not affect the survival of Caenorhabditis elegans, a small nematode that is widely used for toxicity testing and is considered to have high predictive value for toxicity in mammals 75 . However, while clinical potential clearly exists, the assays we report here are most reflective of industrial treatments.…”
Section: Resultsmentioning
confidence: 85%
“…We have previously reported that 5-aryl-2-aminoimidazoles prevent EPS production of S. Typhimurium by reducing the transcription of csgD and its regulon 36 . These compounds can be coated to surfaces-both covalently 14 or in a slow-release matrix 71 to prevent Salmonella biofilm formation in the food industry. Such inhibitors also have clinical potential.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from intensive costs, this leads to high burdens for the patient as well as risks like amputation of the affected limb or even death in case of treatment failure [5,17]. So far, different prevention methods were studied avoiding bacterial adhesion in combination with enhancing osseointegration [18,19] like surface modifications or antimicrobial coatings of implants [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%